Demographic characteristics of optician population in Selangor and their current work arrangement / Nurul Husna Izzatie Md Radzi - Md Radzi, Nurul Husna Izzatie (2015)
The health care system in Malaysia seems to greatly develop since there were increasing community demands on health services. In term of eye health care, the optician was one of the eye practitioners who provide eye health care services to the community. Even though their works were mainly on spectacle dispensing, but the presence of this profession was undeniably helps in managing eye problems among community. This study was done to identify the demographic characteristics of optician population in Selangor according to their geographical distribution, gender, ages and races and also to identify their current work arrangements. All the information of practice address, ages, gender and also races were obtained from the data given by the Malaysian Optical Council (MOC). Meanwhile, to identify their current work arrangement, a self-administered questionnaire was developed to collect information on optician’s current working hours, work status and their workload per day. The questionnaire was randomly distributed to 300 registered opticians in Selangor. Of the 74 respondents, 14 (55.4%) of them were male and 33 (44.6%) of them were female. There were few districts showed undersupply of optician in which they mostly presented with high optician to population ratio. The mean age for male was significantly higher than female as they were mostly dominated in middle (41-60 years) and older age group (61-80 years). Besides, it was clearly showed that this profession was dominated by the Chinese population as compared to other races. In term of their current work arrangement, it was found that the mean working hours for male (59 hours) was slightly higher than female (56 hours). Majority of the respondents were working as full time optician and all of the part time opticians were more likely to be female. Additionally, although opticians in older age had fewer working hours, they were found to have greater number of customers handled per day as compared to the younger and middle age group. In conclusion, there was variation between districts in Selangor on the availability of optician’s services and there were some districts found to have insufficient optician’s services to meet the population needs. In the face of expected increasing demand for eye health care services, a targeted expansion of the workforce appears advantageous in future.